The Role of Transient High-Energy Processes and Atmospheric Turbulence in the Electrical Interaction of Geospheres - Chernogor, L. F. (Kinematics and physics of celestial bodies, 2024)
The mechanism of electrical interaction between subsystems in the Earth–atmosphere–ionosphere–magnetosphere system is currently the least studied and substantiated subject. Moreover, some experts doubt its existence. This study is devoted to investigating the mechanisms of generation and propagation of electric fields that vary in time under the influence of transient high-energy sources of various physical nature and atmospheric turbulence enhanced by these sources, which is an urgent problem. Four options of penetration of electric fields from the atmospheric surface layer into the ionosphere have been proposed. Electrical parameters that depend on disturbances in the electric charge density and the characteristics of atmospheric turbulence have been estimated and numerically calculated for a number of high-energy sources. It is shown that the disturbances arising in the atmospheric surface layer are capable of penetrating into the ionosphere and even into the magnetosphere.